Therapeutic Effectiveness of Galphimia glauca vs. Lorazepam in Generalized Anxiety Disorder. A Controlled 15-Week Clinical Trial - Herrera-Arellano, Armando; Jiménez-Ferrer, Jesus Enrique; Zamilpa, Alejandro; García-Alonso, Griselda; Herrera-Alvarez, Sara; Tortoriello, Jaime (Planta Medica, 2012)
Galphimia glauca Cav. has demonstrated anxiolytic activity attributable to nor-seco-triterpenes denominated galphimines, the most active of which is galphimine-B. Galphimine-B inhibits ventral tegmental area dopaminergic neurons and interacts with the serotoninergic system of the dorsal hippocampus. A previous clinical study that administered a G. glauca herbal medicinal product for 4 weeks evidenced high percentages of therapeutic effectiveness and safety in patients with generalized anxiety disorder. Based on the previous findings, the goal of the present study was to evaluate the effectiveness, safety, and tolerability of G. glauca herbal medicinal product administered during 15 weeks in patients with generalized anxiety disorder. Study design: double-blind, randomized, lorazepam-controlled clinical trial. Study subjects: adult males and females, ambulatory, diagnosed with generalized anxiety disorder, with 20 or more points on the Hamilton anxiety scale, without data of depression, and without anxiolytic treatment in the previous month. Interventions were as follows. Experimental treatment: G. glauca herbal medicinal product in capsules containing the dry extract of G. glauca standardized in 0.175 mg of galphimine-B, one or two capsules twice a day, during 12 weeks plus 3 withdrawal weeks, and control treatment: lorazepam 0.5 mg with the same presentation and posology. Primary outcome: anxiolytic effectiveness (≥ 50 % reduction of initial Hamilton anxiety scale score). Secondary outcomes: tolerability and safety. One hundred ninety-one patients initiated the study with 94 in the experimental group. One hundred four patients concluded the study, 51 of these in the experimental group. Anxiolytic effectiveness, measured as 0 in a negative case and as 1 in a positive case, was assessed 593 times in the experimental group and 631 in the control; the mean effectiveness observed was 0.686 ± 0.019 vs. 0.588 ± 0.019 (repeated-measures ANOVA; p = 0.0003). In the same way, G. glauca-herbal medicinal product diminished the score in the Hamilton anxiety scale to 11.51 ± 8.27 points and lorazepam to 12.40 ± 8.07 points (repeated-measures ANOVA; p = 0.05). The tolerability analysis, which comprised patients who concluded the treatment plus 11 patients who withdrew due to adverse reactions did not show differences between treatments (p = 0.35), nor did therapeutic safety demonstrate differences between groups (p = 0.21). There were no cases of tolerance, intoxication, dependence, or suppression syndrome. We concluded that G. glauca herbal medicinal product, standardized in 0.175 mg of galphimine-B and administered for 15 weeks to patients with generalized anxiety disorder, showed greater anxiolytic effectiveness than that obtained with lorazepam, with high percentages of therapeutic tolerability and safety.
Keywords: Galphimia glauca; Malpighiaceae; nor-seco-triterpenes; herbal medicinal product; generalized anxiety disorder; randomized controlled clinical trial